The melodic structure of Al-Rifai’s praises in Iraq - Al-Sultani, Rabah Hadi Hassan; Zalzala, Ehsan Shakir (Al-Adab Journal, 2022)
Sufi singing or chanting occupies a wide area of ​​the vocal culture of the Iraqi society, as it is one of the most important tributaries of religious music inherited in this society, and on all its occasions and for several purposes from prophetic praise and lament, which is sung in the dhikr gatherings of the takiya for the Sufi orders, and this research sheds light on the One of them is the Rifa’i Sufi hospice and the process of melodic construction of the praises that are sung or sung in. In its theoretical framework, the research dealt with two main topics: (the concept of Sufism and its relationship to art, and Sufi installations), as the concept of Sufism and the most important stages of its emergence and then crystallization were discussed in the first, while the second topic touched on the places where Sufi praises are performed, with a focus on The Qadiriyah and Al-Rifa’i tekkenes, for their historical place in the religious culture of Iraq, as well as being one of the most important places where religious praises are performed in Iraq, whose rituals are still practiced until now. The research also studied randomly selected samples that represented the community represented by the Rifa’i praises by analyzing them with a criterion designed for this purpose, to conclude a set of results and conclusions, the most important of which is that the singing of the Rifa’i praises in Iraq is characterized by the diversity of its maqam scales, especially common in Arab and Iraqi music and singing, with three quarters. The pitch, as it represents the distinctive vocal character of the local environment, and is characterized by the absence of transition between musical genres in the maqam scale, as the focus is on the first gender in order to establish and repeat the melodic idea, and to give the impression of a religious nature, which differs from the mundane, which is characterized by various melodic transitions within The frame of the ladder or the stairs close to it, in addition to that, the singing of Rifa’i praises is characterized by the limited use of melodic structures’ tones, as it is limited to a limited number of ladder tones.